2023
DOI: 10.1002/biot.202300245
|View full text |Cite
|
Sign up to set email alerts
|

Improved adeno‐associated virus empty and full capsid separation using weak partitioning multi‐column AEX chromatography

Wenjun Di,
Kyle Koczera,
Peilun Zhang
et al.

Abstract: Recombinant adeno‐associated virus (rAAV) empty and full capsid separation has been a topic of interest in the rAAV gene therapy community for many years and the anion exchange chromatography (AEX) step has undergone various process optimizations to improve rAAV empty capsid separation, including AEX stationary phase, mobile phase, and process parameters. Here, we present a new AEX method that employs both weak partitioning chromatography (WPC) and multi‐column chromatography (MCC) to achieve improved full rAA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…Di et al recently reported weak partition chromatography of three parallel AEX columns in which rAAV8 full capsids displaced ECs (Di et al, 2023). Di et al's approach increased yield by 20% and increased full capsid levels by 20%, compared to baseline batch chromatography (Di et al, 2023). Our partition approach also leverages the tighter binding of full rAAV9…”
Section: Evaluation and Robustness Testing Of Optimized Aex Processmentioning
confidence: 90%
See 1 more Smart Citation
“…Di et al recently reported weak partition chromatography of three parallel AEX columns in which rAAV8 full capsids displaced ECs (Di et al, 2023). Di et al's approach increased yield by 20% and increased full capsid levels by 20%, compared to baseline batch chromatography (Di et al, 2023). Our partition approach also leverages the tighter binding of full rAAV9…”
Section: Evaluation and Robustness Testing Of Optimized Aex Processmentioning
confidence: 90%
“…For instance, Joshi et al loaded rAAV9 onto POROS 50 HQ with no apparent flow-through, indicating complete binding of all capsid species (Joshi et al, 2021). Di et al recently reported weak partition chromatography of three parallel AEX columns in which rAAV8 full capsids displaced ECs (Di et al, 2023). Di et al's approach increased yield by 20% and increased full capsid levels by 20%, compared to baseline batch chromatography (Di et al, 2023).…”
Section: Evaluation and Robustness Testing Of Optimized Aex Processmentioning
confidence: 99%
“…[22] In laboratory scales, empty particles can be separated from full particles by ultracentrifugation exploiting their slightly different buoyant densities, but this method is not scalable. [23] Anion exchange chromatography has been successfully employed for largescale separation of empty particles from full particles, relying on the difference in isoelectric points between empty and full particles, [24,25] and recent studies have demonstrated improvement in separation of full and empty particles by using weak partitioning chromatography [26] and adjusting mobile phase properties. [27] An ideal new system for rAAV production should be robust, free of virus infection or plasmid transfection, with a high productivity and high full particle content.…”
Section: Introductionmentioning
confidence: 99%